Pengaruh Leverage, Profitabilitas Dan Likuiditas terhadap Nilai Perusahaan pada Sektor Pertambangan Nikel di Indeks Saham Syariah Indonesia (ISSI) Periode 2019-2023 - Sandi, Paradilla; Azhar, Iqlima; Lubis, Nurliza (Jurnal Akuntansi Dan Keuangan West Science, 2025)
This research aims to determine the influence of Leverage, Profitability and Liquidity on Company Value. This type of research is quantitative research. The population in this study was 4 with a sampling technique using purposive sampling with the determination that 3 companies could be researched during the 2019-2023 period. So the number of samples used in this research was 15 samples. Data analysis uses Descriptive Statistics Test, Classical Assumption Test, Normality Test, Autocorrelation Test, Heteroscedasticity Test, Multicollinearity Test, Hypothesis Test, Coefficient of Determination Test (R2), Test, Simultaneous Hypothesis Test (F Test), Partial Hypothesis Test (t Test), and Multiple Linear Regression Test. The research results show that Leverage (X1) has a negative effect on Company Value (Y), Profitability (X2) has no effect on Company Value (Y), and Liquidity (X3) has no effect on Company Value (Y), simultaneously leverage (X1), Profitability (X2), Liquidity (X3) have an effect on Company Value (Y)